Capistrano and the Rails application lifecycle - Loy, Marc (O'Reilly, 2006)
Learn how to make your Rails deployments pain-free with Capistrano! This Short Cut shows you how to use Capistrano to automate the deployment of your Rails applications. It teaches you the basics, but also goes far beyond. It shows you realistic deployment scenarios, including some with complex server farms. It includes a quick reference to Capistrano. As your Rails applications grow, it becomes increasingly important to automate deployment and to keep your development environment well organized. Capistrano is the right tool for the job, and this PDF shows you how to use it effectively.